Dampak Kejelasan Sasaran Anggaran dan Komitmen Organisasi dalam Meningkatkan Kinerja Aparat Pemerintah Daerah Kota Pematangsiantar - Lenny Dermawan Sembiring; Acai Sudirman; Hery Pandapotan Silitonga (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The purpose of this research was (1) to test and analyze the influence of the clarity of the budget targets on the performance of local government. (2) to test and analyze the influence of organizational commitment on the performance of local government. (3) to test and analyze the influence clarity of the budget targets and organizational commitment on the performance of local government. Data were obtained from local government Kota Pematangsiantar. The sample used in this study were 46 local government Kota Pematangsiantar, with respondents of 46 head of department in local government Kota Pematangsiantar. The data were gathered using questionnaires and methods used in this research were multiple linear regression analyses. The results showed that (1) clarity of the budget targets has an influence on the performance of local government Kota Pematangsiantar. (2) organization commitment has an influence on the performance of local government Kota Pematangsiantar. (3) clarity of the budget targets and organizational commitment has an influence on performance local government Kota Pematangsiantar.